Epidemiology of soil-transmitted helminthiases in Malaysia - Ahmed, A.; Al-Mekhlafi, H.M.; Surin, Johari (SEAMEO Regional Tropical Medicine and Public Health Network, 2011)
We reviewed the epidemiology of STH in Malaysia from the 1970s to 2009. High prevalence rates persist among the rural Aborigines, estate workers and in urban slums and squatter areas. Trichuris trichiura is the most prevalent helminth in Malaysia ranging from 2.1 to 98.2. Ascaris lumbricoides follows closely with a prevalence rate of 4.6-86.7, while hookworm is the least prevalent (0-37.0). A countrywide control program with special emphasis on school-based intervention is highly recommended among aboriginal people.